Análise comparativa entre modelos de turbulência utilizando ansys-fluent para obtenção dos coeficientes aerodinâmicos do perfil Eppler 423 - Dantas, Albert Franklin de Moura (Universidade Federal Rural do Semi-Árido, 2017)
The determination of the aerodynamic coefficients of profiles in low Reynolds regimes using computational methods has been gaining great space in the last decades due to the need to reduce time and cost with wind tunnel testing. Thus, this work addresses a comparison of the aerodynamic data provided in experimental tests of the Eppler 423 profile in relation to the data obtained through a computational fluid dynamics analysis. Among the studies, a comparative analysis of the efficiency of the turbulence methods is presented in predicting the separation of the boundary layer and, respectively, the stall at high angles of attack. To obtain the data proposed in this work, the ANSYS® software with FLUENT solver was used, in which a brief mesh study was performed, varying the number of nodes until a constant value was obtained for the 𝑐𝑙, thus considering as ideal mesh for analysis. The work will address finite volume methods, where the three models under study were the Spalart-Allmaras, k-ε Realizable and SST k-ω, selected from their effectiveness in solving low dynamic Reynolds fluid problems. The results showed that the k-ε Realizable model obtained results that were more consistent with the experimental data, but requiring an analysis time up to two times higher than the Spalart-Allmaras model. It was observed that Spalart-Allmaras, among the models, was unique that presented the stalion to the same angle of the experimental data, and with less iterations than the other two models under study. At the end of the paper, the final considerations and suggestions for future work are presented as a way to improve the study of computational fluid dynamics.
Monografia
Keywords: Fluido Dinâmica Computacional (CFD). . . ANSYS®-FLUENT. Aerodinâmica.; Modelos de turbulência; Perfil de alta sustentação; ANSYS®-FLUENT; Aerodinâmica; Dynamic Computational Fluid (CFD). . . ANSYS®-FLUENT. Aerodynamics; Turbulence Models; High lift profile; ANSYS®-FLUENT; Aerodynamics; ENGENHARIAS::ENGENHARIA MECANICA